Homogeneous Condensation in Supersonic Impinging Jets onto Cylindrical Cavity. Issue 5 (October 2013) - Alam, M.M.A.; Setoguchi, T.; Matsuo, S.; Kim, H.D.
Over half a century researchers have engaged themselves in doing research on supersonic impinging jets for their fundamental fluid dynamic perspectives as well as their huge practical applications. In a variety of engineering applications steam or moist air is used as working gas. Rapid expansion of steam or moist air leads to an occurrence of non-equilibrium homogeneous condensation at the region between downstream of nozzle exit and an obstacle. Surrounding gas is heated due to the release of latent heat of condensation, and may affect the jet flow features. The present numerical work deals with the effect of condensation on the aerodynamic and oscillatory flow features of supersonic impinging jets onto a cylindrical cavity. A TVD scheme is used to solve the RANS equations and droplet growth equations for simulating condensation in the jet flowfield. The numerical code is validated through comparison with experimental results. Predicted flow and oscillatory properties of jets are presented.